Mental health in the classroom: a perspective towards the chair of mental education in Colombian schools - Baquero Rozo, Johan Sebastian; Usma Reyes, Yuly Paola (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2022)
For a healthy development it is not only necessary an adequate diet, on the contrary, it is inevitable to have the precise knowledge to strengthen each of the stages of growth that an individual has within a society. In Colombian classrooms there are no guidelines to serve the educational community suffering from some type of mental illness. Despite the fact that in Colombia progress has been made to transform the realities of those who suffer from a mental health illness, no pedagogical guideline has been developed that provides solid structures that lead to establishing support in training contexts, in our research it is made visible how these problems are diagnosed mostly in the most vulnerable communities. He himself investigates quantitative and qualitative aspects of mental health in Colombian schools, making visible the main limitations of the current educational system and the teacher, in search of a strategy that allows the educational community to enrich its human development. Metal health continues to be the black sheep in the creation of laws and public policies, since the lack of implementation and regulations for the prevention of mental health diseases is evident; Due to this, Colombia has been characterized by making the educational system invisible within an articulation with the health system for the training of those individuals who are part of the learning environment.